Identification of a novel and severe pattern of efavirenz drug-induced liver injury in South Africa. (1st June 2016) - Sonderup, Mark W.; Maughan, Debbie; Gogela, Neliswa; Setshedi, Mashiko; Wainwright, Helen; Meintjes, Graeme; Spearman, Wendy
Abstract : Efavirenz now forms part of many antiretroviral regimens in low and middle-income countries. Efavirenz-related drug-induced liver injury is not well characterized but is thought to occur less frequently than with nevirapine. We describe our observation of three defined clinicopathological patterns of injury, one of which, submassive necrosis, is associated with significant morbidity and mortality. A high baseline CD4 +, younger age and possibly female gender, predicts for the injury.